Peran Pokdarwis Teluk Kiluan dalam Pengembangan Desa Ekowisata - Putri, Ashara; Hidayati, Dewi Ayu (Journal of Tourism and Creativity, 2024)
The Ecotourism Village of Teluk Kiluan is an ecotourism destination that applies the concept of "sapta pesona". Visitors to Teluk Kiluan Ecotourism Village do not simply arrive, document their visit, and leave. Instead, they can enjoy the beautiful waters of Teluk Kiluan and are treated to the sight of dolphins in the open sea. This study aims to understand the role of the Tourism Awareness Group (POKDARWIS) of Teluk Kiluan and the challenges faced in managing the ecotourism of Teluk Kiluan. The approach used in this research is descriptive qualitative. Data collection methods include observation, interviews, and documentation. Informants are determined using purposive sampling. Data analysis employs the interactive data analysis model of Miles and Huberman. Data validity is ensured using source triangulation techniques. The conclusion of this study is that the role of POKDARWIS Teluk Kiluan has been quite effective in managing and promoting ecotourism. However, there are still several shortcomings, particularly in terms of infrastructure and facilities, such as the absence of dining facilities and insufficient budget funds.Keywords: Ecotourism, Teluk Kiluan, Tourism Awareness Group, Local Community, Tourist AttractionAbstrakDesa Ekowisata Teluk Kiluan Merupakan Ekowisata yang menerapkan konsep sapta pesona. Pengunjung wisatawan saat berada di Desa Ekowisata Teluk Kiluan tidak hanya datang dan dokumentasi lalu pergi, tetapi dapat menikmati indahnya perairan teluk kiluan dan di suguhkan pemandangan lumba-lumba di tengah lautan. Penelitian ini bertujuan untuk mengetahui peran POKDARWIS Teluk Kiluan serta hambatan terhadap pengelolaan ekowisata Teluk Kiluan. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Metode pengumpulan data berupa observasi, wawancara, dan dokumentasi. Penentuan informan menggunakan purposive sampling. Analisis data menggunakan analisis data interaktif Miles dan Huberman. Validalitas data menggunakan teknik triangulasi sumber. Kesimpulan dari penelitian ini yaitu peran POKDARWIS teluk kiluan sudah berjalan cukup baik dalam pengelolaan ekowisata, dan upaya promosi yang dilakukan. Namun masih terdapat banyak kekurangan, yaitu pada sarana dan prasarana serta fasilitas seperti belum adanya fasilitas tempat makan dan kurangnya dana anggaran.Kata kunci: Ekowisata, Teluk Kiluan, Kelompok Sadar Wisata, Masyarakat Lokal,Objek Wisata